Maternal prebiotic supplementation impacts colitis development in offspring mice - Lê, Amélie; Selle, Amandine; Aubert, Philippe; Durand, Tony; Brosseau, Carole; Bordron, Philippe; Delage, Erwan; Chaffron, Samuel; Petitfils, Camille; Cenac, Nicolas; Neunlist, Michel; Bodinier, Marie; et al. (Frontiers in Nutrition, 2023)
Background and Aims Maternal diet plays a key role in preventing or contributing to the development of chronic diseases, such as obesity, allergy, and brain disorders. Supplementation of maternal diet with prebiotics has been shown to reduce the risk of food allergies and affect the intestinal permeability in offspring later in life. However, its role in modulating the development of other intestinal disorders, such as colitis, remains unknown. Therefore, we investigated the effects of prebiotic supplementation in pregnant mice on the occurrence of colitis in their offspring. Methods Offspring from mothers, who were administered prebiotic galacto-oligosaccharides and inulin during gestation or fed a control diet, were subjected to three cycles of dextran sulphate sodium (DSS) treatment to induce chronic colitis, and their intestinal function and disease activity were evaluated. Colonic remodelling, gut microbiota composition, and lipidomic and transcriptomic profiles were also assessed. Results DSS-treated offspring from prebiotic-fed mothers presented a higher disease score, increased weight loss, and increased faecal humidity than those from standard diet-fed mothers. DSS-treated offspring from prebiotic-fed mothers also showed increased number of colonic mucosal lymphocytes and macrophages than the control group, associated with the increased colonic concentrations of resolvin D5, protectin DX, and 14-hydroxydocosahexaenoic acid, and modulation of colonic gene expression. In addition, maternal prebiotic supplementation induced an overabundance of eight bacterial families and a decrease in the butyrate caecal concentration in DSS-treated offspring. Conclusion Maternal prebiotic exposure modified the microbiota composition and function, lipid content, and transcriptome of the colon of the offspring. These modifications did not protect against colitis, but rather sensitised the mice to colitis development.